Synthesis and cytotoxic activity of some novel 2’-hydroxychalcones containing murrayafoline A - Le Duc Anh,; Luu Van Chinh,; Truong Ngoc Hung,; Nguyen Manh Cuong,; Pham Hong Ngoc, (Vietnam Journal of Science and Technology, 2023)
2’-Hydroxychalcones and murrayafoline A, a natural compounds isolated from Glycomis stenocarpa, have been reported to have the promising anti-cancer activity. In this study, a series of 2'-hydroxychalcones containing murrayafoline A (MuA) 6a-f were achieved by Claisen-Schmidt condensation of the key intermediate 5'-(1-methoxy-3-methyl-carbazolyl)methyl-2'-hydroxyacetophenone 4 with various aldehydes 5a-f with purpose of combining activity of two precusors. Their structures were determined by NMR and MS spectral data. Screening for cytotoxicity of compounds showed that compounds 6a-6d expressed cytotoxic activity, notably compound 6a displayed activity against all tested cell lines LU-1, Hep-G2, MCF-7, P338, and SW480 with the IC50 values ranging from 23.97 to 80.19 μg/mL. Clearly, the substitution at position of N-H group of murrayafoline a led to a decline in the cytotoxicity of the obtained derivatives. This finding suggests the presence of the N-H group might be play a crucial role for the cytotoxicity of the murrayafoline A derivatives.